An identification of the risk factors implicated in diabetic ketoacidosis (DKA) in type 1 and type 2 diabetes mellitus - Sowbakiam Mudly; Virendra Rambiritch; Leyla Mayet (South African Family Practice)
Background: Despite improvements in therapy and disease monitoring, diabetic ketoacidosis (DKA) remains a potentially fatal consequence of diabetes. This retrospective study was undertaken to establish and identify those risk factors that are responsible for the onset of DKA.